Tari Joged Bumbung Klasik Banjar Betngandang Desa Adat Intaran Desa Sanur Kauh Denpasar - Komang Jesha Adi Tangkas; Gusti Ayu Ketut Suandewi; Kompiang Gede Widnyana (Pusat Penerbitan LPPM Institut Seni Indonesia Bali, 2026)
Joged Bumbung is a social dance traditionally performed at the end of the harvest season as a form of entertainment. This art form exists in almost every region of Bali, with variations unique to each locality. In Sanur Village, Denpasar, the dance is known as Joged Bumbung Betngandang, a cultural heritage that has been preserved and transmitted across generations. The Banjar Betngandang Joged Bumbung embodies pregina taksu and features a sacred roll (roll), serving as a testament to its enduring presence in the community. This study employs a qualitative approach to explore three research questions: (1) the historical emergence of Joged Bumbung in Banjar Betngandang, (2) the structural and stylistic form of the dance, and (3) its cultural and social functions. The study applies aesthetic and functional theoretical frameworks. The aesthetic approach analyzes local expressions of beauty in dance movements, costumes, music, and other artistic elements, while the functional approach examines the roles and significance of the performance within the community. The findings indicate that the Joged Bumbung Betngandang is a prominent dance tradition in South Bali, with origins dating back to the 1960s. The dance typically involves four to six performers, maintains the traditional Joged movements and Gamelan music, and preserves the original songs. Functionally, the dance serves as a medium for cultural preservation, entertainment, and educational purposes. The emergence of Joged Bumbung Betngandang is linked to the penglingsir of Banjar Betngandang, who possessed pregina taksu, marking the beginning of this dance tradition. The sacred roll is performed every fifth Full Moon during piodalan, reinforcing its cultural and spiritual significance. Keywords: Joged Bumbung, dance form, function.